APPLYING INVENTORY MANAGEMENT THEORY TO IMPROVE SUPPLY CHAIN MANAGEMENT (SCM) IN PT. ROSYADA HERBA NATURA - raditya ramadhan fajaruddin; abdul haris lahuddin; sentot wahjoe goeritno (Liaison Journal of Engineering, 2023)
Small business is the backbone of this country, but opening a small business can be tricky. Starting a small business can either be the start of something worthwhile or a simple way to lose money. Thus, the implementation of Supply Chain Management is essential for operation in every small business. Supply Chain Management methods to be explored in this research are Inventory Management and CPFR. In order to keep the business running, many businesses establish warehouses where they stock their products. Therefore, to ensure that warehouses continue to operate successfully, businesses need to apply Inventory Management to the warehouse. Factors like Safety Stock, Inventory Tracking, and Cycle Counting can improve the company's Supply Chain Management significantly. Other than Inventory Management, another theory that could improve Supply Chain Management is Collaborative Planning, Forecasting, and Replenishment, also known as CPFR. This is considered the ideal foundation for starting a business. When applying Supply Chain Management, businesses can reduce inventory costs in the future. This creates transparency between the company and supplier due to consistent Reorder Points and EOQ. The purpose of this research is to study PT. Rosyada Herba Natura’s improvement of their Supply Chain Management in terms of Inventory Management and CPFR. Keywords: Small Business, Supply Chain Management, Inventory Management, CPFR,